Why We Should Avoid Artists Who Cause Harm: Support as Enabling Harm - Elicker, Bradley (Journal of Applied Philosophy, 2021)
This article examines our ethical responsibility toward artists engaged in harmful behaviors. Specifically, I demonstrate when and why we are morally obligated to withdraw our public and financial support from Artists Who Cause Harm such as Louis C.K., Terry Richardson, and Ryan Adams. Using a moral distinction presented by Philippa Foot and others, I identify this support as enabling harm when the wealth and influence that we support removes typical barriers that protect victims from harm and interposes barriers that prevent victims from avoiding harm. I proceed to demonstrate that our personal support is morally significant, and we have a moral responsibility to make contributions to collective action when the cost is low or the degree of belief that others will contribute is high. Here we have both a strong belief that others will withdraw support and a relatively low cost to ourselves to do so. I acknowledge that enabling current harms is only a sufficient condition to withdrawing support from an artist and should not minimize other reasons for avoiding certain artists and their works. However, when we do believe that our support enables an artist engaged in harmful behaviors, we have an obligation to withdraw that support.
Keywords: Bibliographie

Accounting For the Limited Success of #MeToo in the Popular Music and Stand-Up Comedy Industries - Worden, Chris; Gjika, Anna (Cultural Sociology, 2023)
Despite several high-profile cases and years of #MeToo activism, a lack of systemic change and consistent consequences for many alleged offenders has led journalists and fans to wonder when the popular music and stand-up comedy industries will truly have their ‘MeToo moment.’ In this article, we explain that this moment has already arrived, but has produced inconsistent results in these industries due to the unique cultural and structural obstacles they share, and which frustrate civil sphere actors’ attempts at civil repair. Our analysis draws on Jeffrey C. Alexander’s (2018, 2019) theory of societalization – the process by which institutional crises come to be seen as social problems that demand the intervention of civil sphere actors. We argue that where #MeToo and the popular music and stand-up comedy industries are concerned, the process of societalization has been (and will likely continue to be) ‘blocked’ or ‘stalled’ (Alexander, 2018, 2019). We suggest that the potential for societalization is reduced due to a combination of the arts sphere’s anti-civil values and weak institutionalization in the popular music and stand-up comedy industries.
Keywords: Bibliographie

“#UsToo”: Empowerment and Protectionism in Responses to Sexual Abuse of Women with Intellectual Disabilities - Boux, Holly Jeanine (Berkeley Journal of Gender, Law & Justice, 2022)
Keywords: Bibliographie; Nettoyer

Québec, un modèle de « safe space » ? - Léger, Souen (Livres Hebdo, 2021)
Face au #metoo qui a secoué l'édition québécoise à l'été 2020, le milieu littéraire a posé des premiers jalons garantissant des rapports exempts de harcèlement et de violences sexuelles. Une réponse rapide, organisée, qui témoigne de la longueur d'avance prise par le Québec sur les enjeux liés au féminisme et à l'inclusion. De quoi séduire les autrices, françaises notamment. Et donner des idées à la France ?
Keywords: Bibliographie; Nettoyer

Vague de dénonciations : un groupe de soutien est créé dans le milieu littéraire - Larouche, Katy (Radio-Canada, 2020)
Keywords: Bibliographie; Nettoyer

Des violences sexuelles et des abus de pouvoir dénoncés dans le milieu littéraire - Bourel, Fanny (Radio-Canada, 2020)
Un groupe de 300 personnes s’est créé pour que les victimes témoignent et pour exprimer des revendications.
Keywords: Bibliographie; Nettoyer

Politique sur le respect des personnes, la prévention et l’intervention en matière de harcèlement - Université du Québec à Montréal (2024)
Keywords: Bibliographie; Nettoyer

Working girl: on selling art and selling sex - Giovannitti, Sophia (Verso, 2023)
"Giovannitti argues that if we delve into our anxieties around art and sex, we can find new ways to live and spaces of freedom"--
Keywords: Bibliographie; Nettoyer

La musique québécoise à l'ère de #MeToo - Caza, Pierre-Etienne (Actualités UQÀM, 2020)
La musicologue Vanessa Blais-Tremblay analyse l’évolution des chansons évoquant des violences à caractère sexuel.
Keywords: Bibliographie; Nettoyer

Naviguer les attentes genrées de la communauté de danse swing de Montréal - Batty, Megan (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Keywords: Bibliographie; Nettoyer

L’opéra, un monde professionnel hanté par les violences de genre - Buscatto, Marie; Helbert, Soline; Roharik, Ionela (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Le 19 août 2020, la soprano Chloé Briot dénonce dans La Lettre du Musicien des agressions sexuelles répétées portées par un collègue chanteur lors de la production de l’opéra L’inondation. Faute d’avoir été entendue et défendue par sa direction, elle annonce encore avoir porté plainte devant la justice française dès le mois de mars de la même année et vouloir ainsi « en finir avec la loi du silence ». Pourquoi l’artiste lyrique n’a-t-elle pas été entendue à plusieurs reprises malgré ses plaintes auprès de ses collègues et de la production ? Dans quelle mesure cette agression sexuelle est-elle symptomatique d’un mode de fonctionnement sexiste plus large du monde de l’opéra français ? Peut-on parler effectivement d’une « loi du silence » dénoncée par la chanteuse ? Si oui, que risquent ceux et celles qui dénonceraient des faits sexistes et des violences sexuelles ?
Keywords: Bibliographie; Nettoyer

#metoo 2.0 to #meNOmore: Analysing Western Reporting About Sexual Violence in the Music Industry - Baker, Andrea; Williams, Katrina; Rodrigues, Usha M. (Journalism Practice, 2020)
In October 2017, #metoo 2.0 reinforces the gendered sexual violence in the creative sector [Marghitu, 2018. “It’s Just art: Auteur Apologism in the Post-Weinstein era”, Feminist Media Studies, 18(93): 491–494] Building on this movement, on 11 November that year, 2912 women “testified about the situation in the Swedish music industry”, signing an open letter condemning sexual violence [Nyheter, 2017. “2192 Women in the Swedish Music Industry Behind Appeal Against Sexism.” Dagens Nyheter, November 17. https://www.dn.se/kultur-noje/2192-women-in-the-swedish-music-industry-behind-appeal-against-sexism/]. After the Swedish initiative, on 12 December 2017, the #meNOmore hashtag was established by 1000 women who signed an open letter to the Australian music industry speaking out against similar behaviour [Whyte, 2017a. “Artists Speak Out Against Sexual Harassment in the Music Industry.” AM – ABC Radio, December 13. https://www.abc.net.au/radio/programs/am/sexual-harassment-in-the-music-industry/9253956]. Using a content analysis framework, this study examines the media framing of 26 stories about #meNOmore by the Western press from 22 November 2017 (height of the Swedish campaign) to 21 December 2017 (a week after the hashtag surfaced in Australia). Research from journalism studies and musicology highlights that sexual violence is historically engrained in the media and music industries. However, findings from our study of the first month’s coverage of the #meNOmore content analysis in 2017 reveal that media reports about women and sexual violence were framed around addressing gender inequality and systemic structural issues in the music industry. This raises the question, has the media has turned a corner when covering sexual violence in the post #metoo era?
Keywords: Bibliographie; Nettoyer

Morinom - Office québécois de la langue française (Grand dictionnaire terminologique, 2022)
Prénom qui a été donné à une personne à sa naissance, mais que celle-ci ne souhaite plus qu'on emploie pour la désigner.
Keywords: Bibliographie; Nettoyer

Impact de la violence sexuelle sur la santé mentale - Centre d’Innovation en Santé Mentale sur les campus (2024)
Keywords: Bibliographie; Nettoyer

Raport de recherche de l'enquête pièces : violences sexuelles en milieu collégial au Québec - Bergeron, Manon; Gagnon, Audréanne; Blackburn, Marie-Ève; M-Lavoie, Dominique; Paré, Caroline; Roy, Sophie; Szabo, Andrea; Bourget, Claudie (Chaire de recherche sur les violences sexistes et sexuelles en milieu d’enseignement supérieur, Université du Québec à Montréal, 2020)
Keywords: Bibliographie; Nettoyer

La relation de pouvoir entre un professeur et ses étudiantes - Radio-Canada (Tout un matin, 2022)
Tout un matin | L'ex-professeur de littérature Samuel Archibald aurait commis des « violences à caractère sexuel » et du « harcèlement sexuel » envers deux étudiantes avec lesquelles il était en situation d'autorité en tant que directeur de maîtrise. Le lien d'emploi entre l'auteur et l'Université du Québec à Montréal (UQAM) aurait été rompu l'année dernière. Au micro de Tout un matin, Rachel Chagnon, professeure au Département des sciences juridiques de l'UQAM, définit ce qu'est une relation de pouvoir entre un enseignant et un étudiant (ce sont majoritairement des femmes), principe qui se trouve au cœur de la politique de l'université pour prévenir et combattre les violences à caractère sexuel.
Keywords: Bibliographie; Nettoyer

Californie: Un professeur de musique de McGill poursuivi pour agression sexuelle - Siag, Jean (La Presse, 2024)
Un professeur de musique de l’Université McGill est poursuivi au civil aux États-Unis par deux anciennes étudiantes disant avoir été agressées sexuellement à l’époque où il enseignait en Californie. Des allégations que le professeur nie vigoureusement.
Keywords: Bibliographie; Nettoyer

Dénoncer le harcèlement dans le milieu de l'improvisation - Radio-Canada (D'Est en Est, 2020)
Keywords: Bibliographie; Nettoyer

L'intimidation et la cyberintimidation au Québec: portrait à partir de l'Étude québécoise sur les rapports sociaux dans un contexte scolaire, de travail et dans la communauté 2022 - Aranibar Zeballos, Daniela; Paquette, Jesseca (Institut de la statistique du Québec, 2024)
Keywords: Bibliographie; Nettoyer

Entente collective entre l'Union des artistes et l'Association québécoise de la production médiatique (Artistes interprètes) (2020)
Keywords: Bibliographie; Nettoyer

Edgar Fruitier est libre après moins d’un mois de prison - Radio-Canada (Radio-Canada, 2022)
Son risque de récidive est jugé faible en raison de son état physique et mental.
Keywords: Bibliographie; Nettoyer

Michel Venne devra finalement prendre le chemin de la prison - Marin, Stéphanie (Le Devoir, 2024)
Keywords: Bibliographie; Nettoyer

Sans consentement : trente scandales sexuels qui ont changé le Québec - Morin, Michel (2024)
Depuis l'arrivée de #MoiAussi et des autres mouvements de libération de la parole, on a assisté au Québec à une succession de scandales sexuels impliquant des personnalités publiques, figures respectées et influentes qui avaient abusé de leur pouvoir, parfois des décennies durant. Michel Morin fait un pas de côté pour revisiter ces histoires encore sensibles, en portant une attention particulière à leur traitement médiatique. Avocat de formation, il se penche aussi sur le fonctionnement du système judiciaire et son impact sur le processus de dénonciation. Sans s'ériger en juge, l'auteur laisse parler les faits, bien souvent accablants, dans un essai qui permet de prendre la mesure de ce qui a été trop longtemps ignoré, voire toléré, et du chemin qui reste à parcourir.
Keywords: Bibliographie; Nettoyer

Stratégie en matière de justice autochtone : Ce que nous avons appris Phase 1 de la mobilisation dirigée par le ministère de la Justice Canada - Ministère de la justice Canada (2023)
Keywords: Bibliographie; Nettoyer

Justice réparatrice en matière de violence conjugale : Enjeux et recommandations - Conseil du statut de la femme (2024)
Keywords: Bibliographie; Nettoyer

L'artiste et son oeuvre - McEwen, Jérémie (2022)
Keywords: Bibliographie; Nettoyer

Dénoncé en ligne, Yann Perreau est lui aussi largué par sa maison de disques - Radio-Canada (Radio-Canada, 2022)
Keywords: Bibliographie; Nettoyer

Le jour où Éric Salvail est tombé - Bourgault-Côté, Guillaume (Le Devoir, 2020)
Keywords: Bibliographie; Nettoyer

Prix Artis : le retrait de la nomination de Maripier Morin confirmé par TVA | Radio-Canada - Radio-Canada (Radio-Canada, 2021)
Keywords: Bibliographie; Nettoyer

Simple Plan renvoie son bassiste de tournée suite à des allégations d’inconduites sexuelles contre lui - Bibeault, Matt (99scenes, 2020)
C’est la firme de management de Simple Plan, Coalition Music, qui a confirmé la nouvelle. Chady Awad avait justement remplacé David Desrosiers lorsque ce dernier avait pris une pause de SP pour traiter sa dépression de 2017 à 2019. Awad était également photographe et vidéaste pour Simple Plan. Simple Plan a mis fin à sa... View Article
Keywords: Bibliographie; Nettoyer

Philippe Bond était déjà sur des listes noires - Bélanger, Cédric (Le Journal de Québec, 2022)
L'humoriste Philippe Bond était déjà depuis plusieurs années sur la liste noire de grandes organisations culturelles.
Keywords: Bibliographie; Nettoyer

Politique visant à prévenir et combattre les violences à caractère sexuel - École nationale de théâtre du Canada (2022)
Keywords: Bibliographie; Nettoyer

Mettre fin au harcèlement sexuel dans le cadre du travail : Se donner les moyens pour agir - Cox, Rachel; Gesualdi-Fecteau, Dalia; Laflamme, Anne-Marie (Comité chargé d'analyser les recours en matière de harcèlement sexuel et d'agressions sexuelles au travail, 2023)
Keywords: Bibliographie; Nettoyer

Safia Nolin répond à la haine par la musique - Caillou, Annabelle (Le Devoir, 2024)
Se gardant de tout révéler, l’artiste explique qu’elle sera sur scène avec pour seules armes sa guitare et sa voix.
Keywords: Bibliographie; Nettoyer

Poursuite intentée par Gilbert Rozon: La requête de Julie Snyder et Pénélope McQuade rejetée en appel - Morin-Martel, Florence (La Presse, 2022)
La poursuite de Gilbert Rozon réclamant 450 000 $ à Julie Snyder et Pénélope McQuade pour diffamation ira de l’avant. La requête des deux animatrices visant à mettre fin aux procédures, qui relèvent « d’une poursuite-bâillon », selon elles, a été déboutée en Cour d’appel, vendredi.
Keywords: Bibliographie; Nettoyer

De nouveaux gestes déplacés de musiciens dénoncés - Papineau, Philippe (2020)
Keywords: Bibliographie; Nettoyer

Prendre soin de sa santé psychologique en culture avec Florence Morin-Parent, psychologue (Le répondeur de l'industrie musicale, 2024)
Keywords: Bibliographie; Nettoyer

Vague de suicides chez les artisans de la scène: Quand le rideau tombe à jamais - Blais-Poulin, Charles-Éric; Groguhé, Marissa (La Presse, 2022)
Keywords: Bibliographie; Nettoyer

Étude sur l’expérience des adultes ayant reçu des services dans le cadre d’un processus judiciaire : Dossiers judiciarisés entre juillet 2020 et juin 2022 au Québec concernant une infraction commise dans un contexte de violence conjugale ou sexuelle - Institut de la statistique du Québec (2023)
Keywords: Bibliographie; Nettoyer

Intermittents du spectacle - France Travail (2024)
Keywords: Bibliographie; Nettoyer

Cultive, la plateforme du développement professionnel en culture (Cultive, 2024)
Plateforme qui rassemble les offres de formation, les outils et les références pour le développement de votre carrière en culture au Québec.
Keywords: Bibliographie; Nettoyer

Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance - Risner, Doug; Watson, Beccy (Springer International Publishing, 2022)
Keywords: Bibliographie; Nettoyer

Salut ça va ? Dialoguer pour prévenir les violences sexuelles - Clermont-Dion, Léa (Cardinal, 2024)
Dans cet essai coup-de-poing, Léa Clermont-Dion s’adresse d’abord aux adolescents et aux jeunes adultes, à leurs parents et à leurs professeur.es, pour ouvrir la discussion sur les violences à caractère sexuel. Son but : éduquer et sensibiliser pour parvenir à des rapports humains respectueux et égalitaires, toujours en évitant de blâmer qui que ce soit. L’autrice vulgarise les concepts de consentement, de culture du viol, de masculinité toxique et explore la portée du mouvement #MeToo. Elle échange aussi avec des acteurs-clé du monde du sport, dont Laurent Duvernay-Tardif, ainsi qu’avec des intervenants du système de justice et recueille de bouleversants témoignages de victimes.
Keywords: Bibliographie; Nettoyer

T'as juste à porter plainte (2021)
Keywords: Bibliographie; Nettoyer

Léa et Loïc (Parminou: Théâtre socialement engagé, 2024)
Keywords: Bibliographie; Nettoyer

"Droit au but" pour prévenir les violences subtiles (Parminou: Théâtre socialement engagé, 2021)
Keywords: Bibliographie; Nettoyer

Politique de prévention du harcèlement psychologique ou sexuel au travail et traitement des plaintes - Théâtre de la Ligue Nationale d'Improvisation (2020)
Keywords: Bibliographie; Nettoyer

En réponse à : « Check ton verre » - Scène & Sauve (Facebook, 2023)
Keywords: Bibliographie; Nettoyer

Le Centre psychologique pour artistes, un nouvel outil pour le milieu culturel - Renaud, Philippe (Le Devoir, 2024)
Keywords: Bibliographie; Nettoyer

Les artistes remettent en question la distribution de l’argent public en culture - Paré, Étienne (Le Devoir, 2024)
Keywords: Bibliographie; Nettoyer

Capsules sur le harcèlement au travail - Groupe d’aide et d’information sur le harcèlement sexuel au travail de la province de Québec (GAIHST, 2022)
Le Groupe d’aide et d’information sur le harcèlement au travail (GAIHST) lance 5 capsules vidéo dédiées aux travailleurs(euses) du Québec.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Accueil - Opération cocon (2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

ANNULÉ(E): Réflexions sur la cancel culture - Lussier, Judith (Éditions Cardinal, 2021)
Après On peut plus rien dire, vendu à près de 7 000 exemplaires, Judith Lussier s’attaque à la culture de l’annulation avec son nouveau livre Annulé(e). Un brillant essai d’analyse qui, grâce à de nombreux exemples évocateurs et contemporains, fait le point sur un sujet brûlant d’actualité.« Alors que les réseaux sociaux ont permis à plus d’individus de prendre la parole et à différentes réalités d’être enfin nommées, il semble que le terrain discursif soit de plus en plus miné. Nous n’avons jamais pu autant nous exprimer librement, et pourtant, nous avons le sentiment que communiquer ses idées n’a jamais été aussi complexe et risqué. »C’est avec ce point de départ tout en nuances que la journaliste et essayiste Judith Lussier tente de comprendre la cancel culture. Cet essai examine ce phénomène complexe aux contours flous qui sème parfois la panique et alimente de nombreuses chroniques, sans faire l’économie d’une réflexion sur les dynamiques de pouvoir qui dictent sa trajectoire.
Keywords: Bibliographie; Nettoyer

Les professions de la culture et des communications au Québec en 2021 - Lubin, Marc-Ancy (Optique culture, 2024)
Keywords: Bibliographie; Nettoyer

Dancing with Inclusivity: The Importance of Integrating Genderless Terminology into Swing Dance Spaces - Olander, Guinievere.R. (Unbound, 2022)
Keywords: Bibliographie; Nettoyer

Publicizing transgender ballet dancers: a pas de deux of inclusion and reiterative gender norms - Mandradjieff, Mara; Alterowitz, Gretchen (Feminist Media Studies, 2023)
Over the last decade, mainstream media sources from the US and UK have shown an increased interest in topics involving transgender and non-binary populations. Yet, their portrayals of such individuals tend to reaffirm rather than challenge cisnormative ideas surrounding bodies and gender. In this article, we consider this ongoing trend within the highly body-centric, traditionally-gendered artform—classical ballet. With a transgender studies and dance studies lens, we analyze current discourse surrounding the recent move for classical ballet companies and schools to adapt casting and training curricula to better include non-binary dancers. Through these analyses we reveal ways media sensationalizes the transgender body by focusing on information regarding hormone therapy and surgeries, and with the topic of ballet in mind, how this transphobic move becomes intertwined with ballet-specific processes of reshaping the body. We claim that although these popular press pieces contribute to a greater awareness of the lived experiences of transgender and non-binary dancers, they simultaneously reiterate ongoing balletic gender tropes that mark the artform as feminine and designate particular body types and movements to specific binarized genders.
Keywords: Ballet; Bibliographie; Nettoyer; gender; media; non-binary; transgender

How is the Ballet World Including Non-Binary Dancers? - Lund, Rebekah (Dance Major Journal, 2022)
A few pioneers have shown the way, but who will follow?
Keywords: Bibliographie; Nettoyer

Rainbow dancing in Finland and the challenge of transgender inclusion - Kavoura, Anna; Rinne, Santtu (Routledge Handbook of Gender Politics in Sport and Physical Activity, 2022)
Traditionally, partner dances occur between a woman and a man, following rather conservative gender roles and rules. However, as a result of international lesbian, gay, bisexual, transgender, intersex, queer, asexual, allies and more (LGBTIQA+) activism, some social dancing events and competitions have made space for gender and sexual diversity. This chapter focuses on the Rainbow and Same-Sex dancing scene in Finland and its potential and challenges for transgender inclusion. We draw on data collected during the first author’s ethnographic and participatory action research study on trans-inclusive sport spaces and the second author’s experiences as a professional dance teacher and Rainbow trans dancer at both same-sex and mainstream dance competitions. Our findings reveal that the Rainbow dancing movement has helped make dancing more accessible and inclusive for members of the trans community through challenging traditional cis- and heteronormative dance roles and the men-lead/women-follow paradigm. Yet, certain challenges for trans-inclusion persist, such as the transphobic politics and rules of national and international dance associations. In concluding this chapter, we provide recommendations for enhancing access and positive experiences of trans people in dance, DanceSport and sport in general.
Keywords: Bibliographie; Nettoyer

Can Rainbow Become the New Pink? A study of ballet educators’ responses to the advancement of LGBTQ+ rights - Hawkes, Tracey (Researching Education Bulletin : Creative Arts Special Edition, 2023)
Keywords: Bibliographie; Nettoyer

Unsettling homocolonial frames of remembrance: Two-Spirit and Indigiqueer interventions at the museum - Failler, Angela (Memory Studies, 2023)
This article considers a Two-Spirit and Indigiqueer protest at the Canadian Museum for Human Rights as a flashpoint that exposes problems with how memory-making institutions are incorporating lesbian, gay, bisexual, trans and queer issues into their programming and/or collections. The protest brings into relief the museum’s investment in a homocolonial framing of remembrance for the way in which the telling of lesbian, gay, bisexual, trans and queer ‘progress’ is entangled with a settler colonial political economy wherein the tokenistic inclusion of some queers into the sexual citizenry happens alongside the dispossession, devaluing and criminalizing of others. I then undertake some preliminary ‘curatorial dreaming’ upon two other interventions–commentaries uploaded to a digital story bank by a Two-Spirit and an Indigenous queer museumgoer, and the short film Woman Dress by Plains Cree artist TJ Cuthand. Along with the protest, the commentaries and the film unsettle homocolonial frames of remembrance and provide critical openings towards decolonial queer memory work at the museum.
Keywords: Bibliographie; Nettoyer

A Gap in the Narrative: Exploring the Experiences of Trans Dancers Today - Best, Erica (Collège Ursinus, 2021)
Keywords: Bibliographie; Nettoyer

Hypermasculinity Makes the Queer Boy Faint - Alterio, Anthony M. (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Through the lens of personal experience, this chapter provides an exploration of the oft-concealed practices and hypermasculine ideals in dance education. Commercial, concert, and academic dance pedagogy continues to create and perpetuate homophobia that restricts the definition of “boy dancer” to the point of creating a false scarcity and competition to be the most cis-heteronormative male possible. Alterio argues this environment contributes to the perpetuation of discrimination against LGBTQIA+ dancers, the exclusion of non-cis boys, and lack of innovation in the field. Recommendations are offered to those interested in pushing the boundaries of performance and gender identity and a call for institutions to support this work.
Keywords: Bibliographie; Nettoyer

Milieu littéraire : le harcèlement touche une écrivaine sur trois - UNEQ (union des écrivaines et des écrivains québécois, 2020)
L’Union des écrivaines et des écrivains québécois (UNEQ) révèle les résultats d’une enquête menée auprès des autrices et auteurs québécois début octobre. Ces chiffres démontrent sans équivoque le déséquilibre du rapport de force entre les partenaires du milieu, déséquilibre qui mène bien souvent à des comportements inacceptables et à une omerta intolérable.
Keywords: Bibliographie; Nettoyer

Violences sexuelles et abus de pouvoir dans le milieu littéraire : il est plus que temps d’agir - UNEQ (Union des écrivaines et des écrivains québécois, 2020)
L’UNEQ donne son appui à la lettre rédigée par un groupe constitué de plusieurs centaines de femmes et minorités de genre déterminées à faire cesser une situation qui ne peut plus durer dans le milieu littéraire.
Keywords: Bibliographie; Nettoyer

Les pratiques des directrices l'industrie de la musique au Québec pour naviguer entre les exigences multiples de leurs fonctions - Saucier, Myriam (Université du Québec à Montréal, 2023)
Keywords: Bibliographie; Nettoyer

Rachat de Dare To Care par Cœur de pirate : un symbole pour les femmes en musique - Radio-Canada (Radio-Canada, 2021)
La rachat de la maison de disque par Béatrice Martin « a une symbolique très forte ».
Keywords: Bibliographie; Nettoyer

Le mouvement #MoiAussi et ses événements marquants - Pineda, Améli (Le Devoir, 2022)
En octobre 2017 émergeait un mouvement de dénonciation planétaire.
Keywords: Bibliographie; Nettoyer

Julien Lacroix visé par des allégations d’agressions et d’inconduites sexuelles - Pineda, Améli (Le Devoir, 2020)
Neuf femmes racontent avoir été victimes d'agressions ou d'inconduites sexuelles de la part de l'humoriste et comédien.
Keywords: Bibliographie; Nettoyer

Le milieu littéraire ébranlé par le mouvement de dénonciations - Lapointe, Josée (La Presse, 2020)
Le milieu littéraire fait face lui aussi au mouvement de dénonciations lancé il y a une dizaine de jours. Un groupe de 300 autrices et actrices de la chaîne du livre s’est formé de manière privée pour échanger à propos de cas d’inconduites sexuelles dont beaucoup ont été victimes.
Keywords: Bibliographie; Nettoyer

La littérature après #MoiAussi - Hébert-Dolbec, Anne-Frédérique (Le Devoir, 2022)
Le milieu littéraire attend encore des changements structurels importants, cinq ans après le début du mouvement.
Keywords: Bibliographie; Nettoyer

Vague de dénonciations : un an après: Qu’est-ce qui cloche dans le milieu culturel ? - Groguhé, Marissa (La Presse, 2021)
C’était il y a un an. En juillet 2020, une nouvelle vague de dénonciations d’agressions et d’inconduites sexuelles a déferlé sur les réseaux sociaux au Québec. Sans être la seule industrie touchée, le milieu culturel a été secoué par plusieurs scandales. Retour sur cet été de grands bouleversements.
Keywords: Bibliographie; Nettoyer

Between denunciations and precautions: the #Metoo movement in Quebec. A Critical Discourse Analysis of Quebec newspaper coverage in 2020 and 2017 - Glorieux, Charlotte (Université Charles, 2023)
Keywords: Bibliographie; Nettoyer

Une nouvelle accusation contre Eddy Toussaint: Son école de danse change de nom pour se dissocier du chorégraphe - Duhamel, Frédérik-Xavier (La Presse, 2022)
Alors que le chorégraphe Eddy Toussaint fait face à une deuxième accusation d’agression sexuelle, l’école et la troupe de ballet qu’il a fondées prennent leurs distances et changent de nom. Des spectacles ont aussi été retirés de l’affiche dans la foulée des accusations, mais la direction estime qu’il est injuste de pénaliser les danseurs.
Keywords: Bibliographie; Nettoyer

Violences sexuelles et abus de pouvoir dans le milieu littéraire: il est plus que temps d’agir - Déclaration commune (Liberté – Art et politique, 2020)
Déclaration commune
Keywords: Bibliographie; Nettoyer

Vague de dénonciations: des têtes tombent dans le milieu artistique - Bélanger, Cédric (Le Journal de Québec, 2020)
Les dénonciations font tomber Maripier Morin, Bernard Adamus et le patron de Dare To Care.
Keywords: Bibliographie; Nettoyer

Michel Venne coupable d’agression sexuelle - Béland, Gabriel (La Presse, 2021)
L’ancien journaliste Michel Venne a été reconnu coupable mercredi d’agression et exploitation sexuelle sur Léa Clermont-Dion alors qu’elle avait 17 ans. La poursuite espère que ce verdict encouragera d’autres victimes à porter plainte.
Keywords: Bibliographie; Nettoyer

Michel Brûlé reconnu coupable d’agression sexuelle - Béland, Gabriel (La Presse, 2020)
L’éditeur Michel Brûlé a été reconnu coupable mercredi d’agression sexuelle à l’endroit d’une auteure venue le rencontrer pour présenter un manuscrit.
Keywords: Bibliographie; Nettoyer

Best Practices for scenes involving nudity, intimacy, simulated sex and sexual violence - ACTRA (2020)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Personal Safety for Dance (2022)
Personal Safety for Dance exists to develop a dance environment that is free from abuse, open, and supportive for all in dance.
Keywords: Bibliographie; Nettoyer

Je n'en ai jamais parlé à personne - Delvaux, Martine (Éditions Heliotrope, 2020)
«En octobre 2017, devant la vague de témoignages suscitée par le mouvement #moiaussi, j’ai senti une urgence : une fois sorties du silence, nous ne devions pas y retourner. C’est la raison pour laquelle j’ai lancé un appel. Ce livre est une chambre d’échos. Un chœur. Sans déesse ni héroïne en tête, des voix avancent. Nous faisons front commun.» Martine Delvaux «Je n'en ai jamais parlé à personne» : paroles recueillies et agencées par Martine Delvaux
Keywords: Bibliographie; Nettoyer

Un hommage pour Romane Bonnier (2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Harcèlement et inconduites dans le milieu artistique. Quel est mon rôle ? - ADISQ; RIDEAU (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Entente collective 2022-2024 entre l'Orchestre Métropolitain et la Guilde des musiciens et musiciennes du Québec (2022)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Entente collective 2023-2026 entre la Guilde des musiciens et musiciennes du Québec et l'Orchestre l'Agora (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Entente collective 2023 - 2027 entre la Guilde des musiciens et musiciennes du Québec et l’Orchestre symphonique du Saguenay-Lac-Saint-Jean (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Violences conjugales et sexuelles: Formations gratuites (Juripop, 2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Collections - Groupe de recherche et d'intervention psychosociale (GRIP) (GRIP, 2024)
Le GRIP intervient en milieu festif (rave, festival) afin de réduire les méfaits associés à la consommation de drogues et de prévenir ses usages problématiques.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Harcèlement au travail - Commission des normes de l'équité de la santé et de la sécurité du travail (CNESST) (2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Accueil - CRIPCAS (2024)
Centre de recherche interdisciplinaire sur les problèmes conjugaux et les agressions sexuelles
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Les premier·ères coordonnateurs et coordonnatrices d’intimité certifié·es du Québec - Coordination d'intimité Québec (ICCQ, 2023)
Les coordonnateurs et coordonnatrices d'intimité pour le cinéma et la télévision. Formé·e·s par les programmes de certification qui ont établi le standard du rôle à l'international et ailleurs au Canada, Mo Matton, Stephanie Breton et Mimi Côté représentent la branche du Québec d'Intimacy Coordinato
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Diversity, Equity, Inclusion & Belonging Committee (ACTRA National, 2023)
ACTRA National’s Diversity, Equity, Inclusion & Belonging Committee promotes the principles concerning the casting of People of Colour, Indigenous Peoples and people with disabilities. The best initiatives are driven by members. We can better shape initiatives to support you by getting to know our membership and understanding your experiences. We welcome your input and your […]
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Women's Committee (ACTRA National, 2023)
The best initiatives are driven by members. By getting to know the membership and listening to your experiences, we can better shape initiatives that support you. Does your ACTRA Branch have a Women’s Committee? Find out by contacting your Branch office or contact the National Women’s Committee if you would like to get one started. […]
Keywords: Bibliographie; Dans le rapport

Progress Pride Committee (ACTRA National, 2023)
ACTRA National is proud to be launching the ACTRA National Progress Pride Committee. The inaugural Committee meeting took place on Friday, May 26th, 2023. Mandate The mandate of the committee is to address issues that impact the Queer ACTRA membership across the country, and to build a National community through the sharing of relevant information […]
Keywords: Bibliographie; Dans le rapport

Soutien psychologique (Guilde des musiciens et musiciennes du Québec, 2022)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

GRIP-Prévention - Groupe de recherche et d'intervention psychosociale (GRIP, 2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Formations et autres ressources - Conseil des ressources humaines du secteur culturel (Milieux de travail respectueux dans les arts, 2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Kesha’s Comeback and the Stakes of Live Performance: Connecting through Trauma at the 2018 Grammy Awards - Hearfield, Katelyn (Journal of Musicological Research, 2021)
The use of live popular music performance as a platform to address gendered and sexual violence and trauma within the popular music industry can be demonstrated through the analysis of Kesha’s performance of “Praying” at the 2018 Grammy Awards. Analyzing the artist’s vocal and artistic delivery, in addition to her public persona following her allegations of sexual abuse against producer Lukasz Gottwald (Dr. Luke), illustrates how live performance—building on and contrasting with social media campaigns, such as #FreeKesha and #MeToo, and studio recordings—is a uniquely effective mode of processing individual and collective trauma.
Keywords: Bibliographie; Nettoyer

Capsule sur le GRIP, projet Spotlight (YouTube, 2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

L'Aparté - Formation ADISQ (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Capsule Collectif Social - Formation ADISQ (YouTube, 2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Pour une culture du consentement - Les frères Seaborn (2022)
Keywords: Bibliographie; Nettoyer

Porter plainte: récit - Clermont-Dion, Léa (Le Cheval d'août, 2023)
"Agressée sexuellement par son patron à l'âge de dix-sept ans, Léa Clermont-Dion décide, près d'une décennie plus tard, de poursuivre l'agresseur en justice. Elle consignera son expérience dans son journal jusqu'au procès. Pendant ce temps, l'affaire Harvey Weinstein déclenche le mouvement #MeToo, et des millions de femmes dénoncent la culture du viol à visage découvert. La déposition criante de vérité de Porter plainte témoigne de la froide autorité du droit et des luttes des victimes de crimes sexuels, qui reprennent la parole qu'on leur a soustraite"--Back cover
Keywords: Bibliographie; Nettoyer

Le privilège de dénoncer: justice pour toutes les victimes de violences sexuelles - Souffrant, Kharoll-Ann (Éditions du remue-ménage, 2022)
Keywords: Bibliographie; Nettoyer

Faire justice: moralisme progressiste et pratiques punitives dans la lutte contre les violences sexistes - Deck Marsault, Elsa (La Fabrique éditions, 2023)
Keywords: Bibliographie; Nettoyer; Restorative justice; Sexual minorities; Violence against; Women

Le programme Possibilités de justice réparatrice (médiation entre la victime et le délinquant) - Service correctionnel Canada (2020)
Le programme Possibilités de justice réparatrice (médiation entre la victime et le délinquant)
Keywords: Bibliographie; Nettoyer

Réseau d'aide aux hommes pour une société sans violence (À coeur d'homme, 2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Modèle de politique en matière de harcèlement psychologique ou sexuel au travail et de traitement des plaintes - Commission des normes de l'équité de la santé et de la sécurité du travail (CNESST) (2024)
Notre modèle de politique est présentement en cours de révision pour tenir compte des nouvelles dispositions prévues par la Loi visant à prévenir et à combattre le harcèlement psychologique et la violence à caractère sexuel en milieu de travail
Keywords: Bibliographie; Nettoyer

Webinaire contre le harcèlement et les violences (milieu cirque) pour artistes & travailleuses/eurs (2020)
En partenariat avec Juripop, En Piste vous présente le webinaire qui fût présenté dans le cadre de sa clinique contre le harcèlement et les violences dans le milieu cirque, qui a eu lieu le mardi 25 août 2020. Ce webinaire présente les services du Centre d'aide aux victimes d'actes criminels (CAVAC) et du Groupe d'aide et d'information sur le harcèlement sexuel au travail (GAIHST). Pour plus d'information et de ressources, visitez notre site web : www.enpiste.qc.ca
Keywords: Bibliographie; Nettoyer; À ajouter

Pour des milieux de travail exempts de harcèlement - Ordre des conseillers en ressources humaines et en relations industrielles agréés du Québec. (Carrefour RH, 2024)
Guide pour améliorer ses pratiques de prévention, d'intervention et de soutien dans des situations de harcèlement au travail.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Rebâtir (2023)
Consultation juridique sans frais pour les personnes victimes de violence sexuelle et de violence conjugale.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Commande un Angelot (2021)
« Le protocole d’accréditation Commande un Angelot a été conçu afin de s’attaquer aux violences à caractère sexuel dans les bars et les événements festifs ou sociaux. Celui-ci vise à prévenir ces situations et à venir en aide aux personnes en difficulté. Le Collectif social, un organisme sans but lucratif qui souhaite déployer et soutenir la réalisation d’initiatives de nature communautaire ou sociale qui répondent aux besoins des communautés étudiantes des établissements d’enseignement supérieur, est derrière ce projet. »
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Code d'éthique - Association québécoise de l'indusstrie du disque, du spectacle et de la vidéo (ADISQ) (2023)
Keywords: Bibliographie; Nettoyer

Déclaration pour un environnement de travail exempt de harcèlement dans le milieu culturel québécois (Regroupement des arts interdisciplinaires du Québec, 2024)
ATTENDU QUE des associations d’artistes et des associations de producteurs (ci-après collectivement les « Associations ») ainsi que les regroupements du milieu culturel (ci-après collectivement les « Regroupements »), conviennent que toutes les personnes œuvrant dans le milieu culturel québécois, quel que ce soit leur rôle ou leurs responsabilités, devraient être en mesure d’exercer [...]
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Dénoncez un incident sur le plateau (ACTRA Montreal, 2024)
Grâce aux rapports anonymes, nous sommes informés des problèmes au fur et à mesure qu’ils surviennent. Il est possible de rester anonyme, mais il est préférable de laisser vos coordonnées pour que nous puissions vous contacter. Nous ne donnerons jamais suite à une réclamation sans votre consentement!
Keywords: Bibliographie; Nettoyer

Coordonnateur·rice·s de l'intimité - ACTRA Montréal (ACTRA Montreal, 2024)
Les coordonnateurs d'intimité sont des spécialistes de la production qui planifient, supervisent et coordonnent les scènes intimes filmées.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Faire face au harcèlement en milieu de travail culturel: Un rapport sur les mécanismes de dénonciation et d’enquête existants et potentiels pour travailleurs et employeurs culturels - Labine, Lise; LeSage, Jeanne; Gagnon, Grégoire (Conseil des ressources humaines du secteur culturel, 2020)
Keywords: Bibliographie; Coffre à outils; Nettoyer

Tous les spectacles (Parminou: Théâtre socialement engagé, 2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Campagne de sensibilisation : Harcèlement au travail - Groupe d’aide et d’information sur le harcèlement sexuel au travail de la province de Québec (GAIHST, 2023)
GAIHST Inc est un organisme communautaire de la province de Québec qui vient en aide aux travailleurs et travailleuses ayant subi du harcèlement au travail.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

En mouvement vers une culture du consentement (RQCALACS, 2024)
Les CALACS offrent des services de soutien aux victimes d’agressions à caractère sexuel. Trouvez de l’aide, partout à travers le Québec.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Contribuer à une culture exempte de harcèlement (SST) - AQTIS 514 IATSE (L'Alliance québécoise des techniciens et techniciennes de l'image et du son, section locale 514, 2024)
« Parce que la sécurité au travail est une responsabilité collective, luttons ensemble pour éliminer le harcèlement ! Votre syndicat a fait de cet enjeu sa priorité. Notre industrie, atypique et fortement compétitive, peut engendrer de nombreux abus et freiner la dénonciation. La précarité d'emploi, la hiérarchisation des fonctions, le taux de rendement exigé, le niveau de stress et la crainte de représailles en sont les principaux facteurs. L'AQTIS 514 IATSE met à votre disposition une formation gratuite et interactive pour vous aider à travailler dans un environnement sécuritaire. OBJECTIFS : Reconnaître les situations qui s’apparentent à du harcèlement psychologique ou sexuel au travail; Savoir adopter une posture d’affirmation face à des conduites d’incivilité, d’intimidation ou de harcèlement en vue de les faire cesser; Connaître les mécanismes pour signaler ou dénoncer les conduites s’apparentant à de l’intimidation ou du harcèlement.»
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Centre d'aide aux victimes d'actes criminels (CAVAC, 2024)
«Le Réseau des CAVAC est présent dans toutes les régions du Québec. Plus de 185 portes qui vous donnent accès à des professionnel(le)s formé(e)s en intervention ».
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Prévenir et gérer le harcèlement - Formations AQPM (Formations : Des classes de perfectionnement pour les professionnel-(le)s de l'industrie audiovisuel, 2023)
« Cette formation permettra aux producteurs et à leurs représentants de reconnaître les situations de harcèlement ou celles qui sont à risque de le devenir afin de comprendre les rôles et responsabilités qui leur reviennent. Les particularités propres à notre industrie y seront également abordées. Formateur: Me Frédéric Massé Borden, Ladner, Gervais »
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Collectif social collective - Le Collectif social (Lutte contre les violences sexuelles, 2023)
Offrent des formations sur mesure, ainsi que les formations : - Prévenir la violence sexuelle dans les événements festifs ou sociaux - Les violences sexuelles chez les communautés LGBTQIA2S+ - Devenir un témoin actif
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Code d'éthique - Association nationale des éditeurs de livres (ANEL) (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Code de conduite [Affiche] (2024)
18 x 24 harcèlement affiche WEB
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Inconduite sexuelle: deux acteurs largués - Gendron-Martin, Raphaël (Le Journal de Montréal, 2020)
La valse des dénonciations pour inconduite sexuelle touchant le milieu culturel se poursuit.
Keywords: Bibliographie; Nettoyer

Safia Nolin accuse, Maripier Morin s’excuse - Groguhé, Marissa (La Presse, 2020)
L’auteure-compositrice-interprète Safia Nolin a provoqué une onde de choc en accusant mardi Maripier Morin de s’être livrée à du harcèlement sexuel, d’avoir commis une agression physique et d’avoir proféré des propos racistes lors d’une soirée dans un bar il y a deux ans. Des allégations en partie admises par l’animatrice télé, qui a présenté ses excuses le lendemain.
Keywords: Bibliographie; Nettoyer

Le milieu du jeu vidéo est-il indécrottablement discriminatoire? - Baillargeon, Stéphane (Le Devoir, 2020)
Le mouvement #MoiAussi frappe l’industrie de la manette et son sexisme systémique.
Keywords: Bibliographie; Nettoyer

La Cour d’appel donne raison à Gilbert Rozon - Corriveau, Jeanne (Le Devoir, 2020)
Le tribunal a annulé l’autorisation de l’action collective des Courageuses contre l’ancien magnat de l’humour.
Keywords: Bibliographie; Nettoyer

Rethinking sexual violence labels: exploring the impact of ‘victim’ and ‘survivor’ discourse - O’Shea, Brittany; Feicht, Rebecca; Brown, Marion; Numer, Matthew (European Journal of Psychotraumatology, 2024)
Background: Universities’ responses to sexual violence have faced scrutiny for their lack of proactiveness and their failure to address campus socio-cultural norms that contribute to rape myth acceptance. The labels victim and survivor play a crucial role in shaping attitudes toward sexual violence, but there is limited research on how university students perceive these labels. Objective: This paper explores sexual violence labels and their role in perpetuating rape culture. Undergraduate university students’ beliefs on using the label survivor instead of victim to describe someone who has experienced sexual violence were examined to consider how these labels create societal discourse on sexual violence. Method: The study draws on qualitative data collected from undergraduate students in Canada and the United States through open-response questions in an interactive textbook. Data were analysed and interpreted using a multi-method approach that combined principles of Critical Discourse Analysis and Feminist Poststructuralism. Direct quotes and word clouds from participants’ responses are used as evidence and to visually display discourse. Results: Findings revealed that participants recognised the negative societal discourses associated with the label victim and supported using survivor to challenge perceptions of sexual violence. Despite this, participants expressed hesitancy to adopt the label survivor because of the potential negative implications, such as the label promoting the allocation of individual blame, increasing barriers to justice, and reducing the perceived severity of sexual violence. Conclusions: This study underscores the complexities of sexual violence labels, the influence of language in shaping societal perceptions, and the need for a more comprehensive and equitable approach to responding to sexual violence. Dichotomy of Labels and Nuanced Perceptions: Sexual violence labels shape identity perceptions. Participants dichotomised the labels victim and survivor, associating one with negative attributes and the other with positive attributes. However, nuanced views of how people perceive and identify with these labels challenge distinct categories. Victims being negatively perceived, while survivors are admired for their resiliency highlights complexities in societal expectations that may not fully address the underlying determinants of sexual violence.Role of Language in Reproduction of Rape Culture: Poststructuralist theories emphasise the role of language in the production and maintenance of discourse. The study shows that victim discourse is steeped in rape myths. The historical discourse surrounding the label may contribute to the perpetuation of negative attitudes and behaviours toward victims of sexual violence. The emergence of the label survivor reflects a societal shift, but findings suggest this may lead to societal complacency towards sexual violence.Spectrum of Severity and Societal Empathy: Participants’ understanding of sexual violence as a spectrum of severity may lead to unequal levels of empathy and support. This discourse creates positions of dominance and oppression, potentially marginalising certain groups who are disproportionately affected by sexual violence. The study highlights how severity discourse can influence institutional agendas and may result in political and institutional neglect of sexual violence. Dichotomy of Labels and Nuanced Perceptions: Sexual violence labels shape identity perceptions. Participants dichotomised the labels victim and survivor, associating one with negative attributes and the other with positive attributes. However, nuanced views of how people perceive and identify with these labels challenge distinct categories. Victims being negatively perceived, while survivors are admired for their resiliency highlights complexities in societal expectations that may not fully address the underlying determinants of sexual violence. Role of Language in Reproduction of Rape Culture: Poststructuralist theories emphasise the role of language in the production and maintenance of discourse. The study shows that victim discourse is steeped in rape myths. The historical discourse surrounding the label may contribute to the perpetuation of negative attitudes and behaviours toward victims of sexual violence. The emergence of the label survivor reflects a societal shift, but findings suggest this may lead to societal complacency towards sexual violence. Spectrum of Severity and Societal Empathy: Participants’ understanding of sexual violence as a spectrum of severity may lead to unequal levels of empathy and support. This discourse creates positions of dominance and oppression, potentially marginalising certain groups who are disproportionately affected by sexual violence. The study highlights how severity discourse can influence institutional agendas and may result in political and institutional neglect of sexual violence.
Keywords: Bibliographie; Nettoyer

Gros été pour la culture du viol - Elkouri, Rima (La Presse, 2022)
Nouveau scandale de viol collectif à Hockey Canada. Allégations d’inconduites sexuelles contre l’humoriste Philippe Bond. Absolution conditionnelle pour l’ingénieur Simon Houle coupable d’agression sexuelle…
Keywords: Bibliographie; Nettoyer

Quand se taire n’est plus une option - Papineau, Philippe; Renaud, Philippe (Le Devoir, 2020)
Keywords: Bibliographie; Nettoyer

Ubisoft : les démissions ne viendront pas à bout de la toxicité, disent des employés - Prévost, Hugo (Radio-Canada, 2020)
Le géant du jeu vidéo est plongé dans la tourmente depuis des semaines en raison d'allégations de harcèlement.
Keywords: Bibliographie; Nettoyer

Vague de dénonciations : au tour du cirque de faire son examen de conscience - Siag, Jean (La Presse, 2020)
Depuis quelques semaines déjà, les témoignages de violences sexuelles dans le monde du cirque se multiplient sur les réseaux sociaux. Au point où le regroupement national des arts du cirque, En Piste, a décidé de lancer dès mardi avec Juripop une clinique « contre le harcèlement et les violences dans le milieu du cirque ». La Presse a parlé aux instigateurs de Victims_Voices_Circus, espace virtuel où la parole de nombreuses artistes s’est fait entendre.
Keywords: Bibliographie; Nettoyer

Harcèlement à Ubisoft : la joueuse professionnelle Stéphanie Harvey témoigne - Agence France-Presse (Radio-Canada, 2020)
Une vague de dénonciations secoue Ubisoft et l'industrie du jeu vidéo depuis quelques semaines.
Keywords: Bibliographie; Nettoyer

Pollitique contre le harcèlement et l’intimidation et la promotion d’un environnement sain - École nationale de théâtre du Canada (Département du bureau de la direction générale, 2023)
Keywords: Bibliographie; Nettoyer

Cadre de référence évolutif des objectifs et contenus de prévention des violences à caractère sexuel en milieu d’enseignement supérieur - Fradette-Drouin, Laurie; Bergeron, Manon (Chaire de recherche sur les violences sexistes et sexuelles en milieu d’enseignement supérieur. Université du Québec à montréal, 2022)
Keywords: Bibliographie; Nettoyer

Violence sexuelle - Bureau de la médiation et du signalement (Université McGill, 2024)
Tous les membres de McGill ont droit au soutien sans équivoque du Bureau d’intervention, de prévention et d’éducation en matière de violence sexuelle (OSVRSE – Office for Sexual Violence Response, Support, and Education), que ces membres déposent ou non un signalement officiel. L’OSVRSE peut vous fournir des services de soutien, vous aider à obtenir des accommodements scolaires ou professionnels et vous expliquer les différents processus de signalement — que vous envisagiez de faire un signalement dans le cadre de la Politique contre la violence sexuelle de McGill ou à l’extérieur — afin que vous puissiez décider ce qui vous convient le mieux. Il n’est pas nécessaire de déposer un signalement officiel pour accéder à du soutien, demander des accommodements possibles ou obtenir de l’information auprès de l’OSVRSE. Vous pouvez prendre rendez-vous directement avec l’OSVRSE ici. Si vous souhaitez déposer un signalement en vertu de la Politique contre la violence sexuelle de McGill ou en apprendre davantage au sujet des processus offerts (médiation/enquête), veuillez communiquer avec le Bureau de la médiation et du signalement (OMR). Visitez notre page Demander une consultation pour en savoir plus. Tous les membres de la communauté universitaire ont le droit de travailler et d’apprendre dans un environnement exempt de violence sexuelle. L’Université reconnaît que, même si la violence sexuelle touche tous les membres de la société, ce type de maltraitance et ses conséquences peuvent atteindre de manière disproportionnée des membres de groupes sociaux aux prises avec des formes intersectionnelles de discrimination systémique ou d’obstacles (fondés notamment sur l’identité et l’expression sexuelles, l’orientation sexuelle, la race, la religion, l’appartenance à un groupe autochtone, l’ethnicité, l’invalidité ou la classe sociale).  Qu’est-ce que la violence sexuelle ? La violence sexuelle est un terme générique qui désigne un continuum d’actes de nature sexuelle qui sont menacés, tentés ou commis à l’encontre d’une personne sans son consentement. Elle peut être dirigée vers l’orientation sexuelle, l’expression sexuelle ou de genre ou l’identité de genre d’une personne. Cela inclut l’agression sexuelle, le harcèlement sexuel, le harcèlement criminel, la cyberviolence, la distribution non consensuelle d’images sexuelles, le voyeurisme, etc. L’OSVRSE de McGill présente de plus amples renseignements sur la violence sexuelle sur son site Web. Définition dans la politique La définition officielle de la violence sexuelle adoptée à McGill se trouve à l’alinéa 7k) de la Politique contre la violence sexuelle de McGill : « Violence sexuelle » s’entend d’un ou de plusieurs actes sexuels, commis ou tentés, qui ciblent la sexualité, l’identité ou l’expression sexuelle d’une personne, ou toute menace de commettre de tels actes contre une personne sans son consentement. La violence sexuelle peut se manifester en personne, au téléphone ou en ligne. Elle englobe : i) l’agression sexuelle qui désigne un contact sexuel avec une autre personne sans son consentement; ii) le harcèlement sexuel, qui désigne une conduite de nature sexuelle A) selon laquelle l’activité sexuelle : est établie comme modalité ou condition explicite ou implicite d’emploi d’une personne ou de statut dans un cours, un programme ou une activité; ou  est utilisée comme motif sous-tendant une décision en matière d’emploi ou d’éducation qui a des incidences sur une personne; OU, B) qui a pour effet de nuire au travail ou au rendement universitaire d’une personne quand il est reconnu, ou devrait être reconnu, que cette conduite est importune;  iii) « traquer » qui désigne la surveillance ou le fait de suivre indûment une autre personne alors que cette personne, déposant une divulgation ou un signalement, a l’impression que cette traque a un lien avec le sexe ou l’identité sexuelle; iv) « exhibitionnisme » qui désigne l’exposition de ses organes sexuels à une autre personne dans un lieu public ou de manière menaçante ou choquante pour cette personne; v) « voyeurisme » qui désigne l’observation furtive ou l’enregistrement d’une personne au moyen d’un dispositif mécanique ou électronique; vi) « diffusion d’images sexuelles » qui désigne la distribution d’une image, photo ou vidéo de nature sexuelle d’une personne sans son consentement; et vii) « exploitation sexuelle » qui désigne l’abus ou l’exploitation de la sexualité d’une autre personne aux fins d’une gratification sexuelle, d’un gain pécuniaire, d’un avantage personnel ou à tout autre fin non légitime.
Keywords: Bibliographie; Nettoyer

Un projet pilote pour réduire les risques d’intoxication et pour prévenir la consommation excessive (Éduc'alcool, 2023)
Montréal, le 21 avril 2023 – Éduc’alcool et le Service de police de la Ville de Montréal (SPVM) ont lancé hier le projet pilote Touche pas à mon verre* en présence du ministre de la Sécurité publique du Québec, M. François Bonnardel. Cette initiative prend la forme d’une distribution gratuite de 10 000 protège-verres afin de, notamment, […]
Keywords: Bibliographie; Dans le rapport; Nettoyer

Check tes chums - Massé, Manon (Facebook, 2023)
Keywords: Bibliographie; Nettoyer

Au-delà des « vagues » #moiaussi : cinq ans de mobilisation féministe en musique au Québec (2017–2022) - Blais-Tremblay, Vanessa; Champagne, Lysandre (Intersections, 2023)
Cet article dresse le portrait de cinq organisations qui militent pour l’équité en musique au Québec depuis 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL et le réseau DIG! Différences et inégalités de genre dans la musique au Québec. En s’inscrivant d’abord dans la longue lignée des travaux critiques en historiographie féministe, l’article rend compte de la pluralité des mobilisations féministes et ce, au-delà des « vagues » #moiaussi qui ont ponctué l’actualité musicale québécoise au cours des cinq dernières années (2017–2022). Dans la seconde partie, les autrices détaillent les travaux du réseau D!G , lancé en avril 2021 par Vanessa Blais-Tremblay, et présentent des retombées initiales prometteuses à la fois pour le milieu universitaire et pour les milieux de pratique en ce qui concerne l’épistémologie et les méthodologies de la « musicologie partenariale collaborative féministe ». , This article profiles five organizations that have been advocating for equity in Quebec music since 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL and D!G Différences et inégalités de genre dans la musique au Québec. In line with a long tradition of critical work in feminist historiography, the authors first account for the diversity of feminist mobilizations in Quebec music beyond the #metoo “waves” which have received significant media attention over the past five years (2017–2022). In the second part, the authors detail the development of the D!G network, a feminist collaborative research partnership launched in April 2021 by Vanessa Blais-Tremblay, and its contributions to both Quebec’s music industry and to feminist partnership research epistemologies and methodologies.
Keywords: Bibliographie; Nettoyer

Accueil - Juripop (L'Aparté, 2023)
L'Aparté offre des services juridiques gratuits à toute personne ayant vécu du harcèlement dans le milieu de la culture partout au Québec
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Les femmes dans l’industrie musicale canadienne francophone - Bissonnette, Joëlle (Musicaction, 2022)
Keywords: Bibliographie; Nettoyer

Mémoire présenté à la Commission de l’économie et du travail Dans le cadre des consultations particulières et des auditions publiques sur le projet de loi n° 42 - Loi visant à prévenir et à combattre le harcèlement psychologique et la violence à caractère sexuel en milieu de travail - Juripop (2024)
Keywords: Bibliographie; Nettoyer

Expériences de comportements sexualisés inappropriés, d’agressions sexuelles et de discrimination fondée sur le genre vécues par les travailleurs dans les provinces canadiennes, 2020 - Burczycka, Marta (Statistique Canada, 2020)
Keywords: Bibliographie; Nettoyer

3 M$ à Juripop pour venir en aide aux victimes de harcèlement et de violence dans le milieu culturel - Cabinet du ministre de la Culture et des Communications et ministre responsable de la Jeunesse (Gouvernement du Québec, 2023)
Keywords: Bibliographie; Dans le rapport; Nettoyer

*Loi visant à harmoniser et à moderniser les règles relatives au statut professionnel de l'artiste - Gouvernement du Québec (LQ2022, c 20, 2022)
Keywords: Bibliographie; Nettoyer

Révision des lois sur le statut de l'artiste - Cabinet du ministre de la Culture et des Communications et ministre responsable de la Jeunesse (Gouvernement du Québec, 2022)
QUÉBEC, le 3 juin 2022 /CNW Telbec/ - L'Assemblée nationale du Québec a adopté à l'unanimité aujourd'hui le projet de loi numéro 35, Loi visant à moderniser et à harmoniser les règles relatives au statut professionnel de l'artiste, déposé par la ministre...
Keywords: Bibliographie; Nettoyer

Avantage pour membre - Assocation canadienne des humoristes stand-up, Sketch & Impro (AQHS, 2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Theatre-making in the age of #MeToo: Working cross-culturally toward a framework for making safer creative spaces - Park, Younghee (Université de technologie du Queensland, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

For the Love of Music: Ending Sexual Harassment in the Music Industry - Musicians’ Union (2021)
Keywords: Bibliographie; Nettoyer

Raising Their Voices: Independent Review into Sexual Harm, Sexual Harassment, and Systemic Discrimination in the National Music Industry - Shehadie, Alexandra; The Review Team (Support Act, 2022)
Keywords: Bibliographie; Nettoyer

Accusations d’agression sexuelle et de diffamation: Jasmin Roy réplique et poursuit en diffamation Jean-François Robillard - Dussault, Lila (La Presse, 2023)
Un duel de poursuites en diffamation est en cours entre l’acteur Jasmin Roy et un homme qui l’accuse d’agression sexuelle, Jean-François Robillard. L’affaire a pris racine dans la foulée du mouvement #metoo, en 2020. Elle remonte à une soirée dans un bar d’Abitibi-Témiscamingue, 20 ans plus tôt.
Keywords: Bibliographie; Nettoyer

Une présumée victime d’agression sexuelle poursuivie en diffamation pourra rester anonyme - Marin, Stéphanie (Le Devoir, 2022)
Au coeur de la poursuite : une publication dénonçant l’humoriste Alexandre Douville sur la page Dis son nom.
Keywords: Bibliographie; Nettoyer

Comedy’s double killjoy: workers’ DIY strategies to address harassment and precarity in the comedy industry - Trusolino, Madison; Ships, Diandra (Feminist Media Studies, 2023)
Since 2017, the #MeToo movement has highlighted gender-based violence and harassment in the comedy industry, where those comedians affected have little to no workplace infrastructure to lean on. Because comedy clubs are described as venues rather than sites of work, comedy workers are not technically employees and are not protected by workplace safety laws nor supported by professional organizations or unions. We argue that the lack of a formal workplace and its related precarity exacerbates violence against women, queer, transgender, disabled, and/or workers in the Canadian and American comedy industries, pushing comedy workers to enact do-it-yourself workplace safety strategies to protect themselves and one another. We describe these protective, caring activities as akin to Brenda Parker’s “double killjoy,” and push our understanding of creative work into places of public resistance and life-making.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Plan de lutte contre les violences et le harcèlement sexistes et sexuels dans le spectacle vivant - Ministère de la Culture français (2021)
Keywords: Bibliographie; Nettoyer; Raphaël

The Royal Court in the Wake of #MeToo - Fallow, Catriona; Mullan, Sarah Jane (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Supporting Brave Spaces for Theatre-​Makers Post-#MeToo: A Chicago-Based Study on Rehearsing and Performing Intimacy in Theatre - Studham, Susan Fenty (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Krytyczki as Activists: On Theatre Criticism, Affect, Objectivism and #MeToo in Polish Drama Schools: Interview with Monika Kwaśniewska - Lech, Kasia (Critical Stages/Scènes critiques, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

We Get It: Calling Out Sexism and Harassment in Australia’s Live Performance Industry - Thomasson, Sarah (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

The Change You Want to See: Results of the first-ever survey of workplace sexual harassment in the Canadian performing arts, film, and television industries - Aftermetoo (2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Analysis of the “Regional Survey on Violence and Harassment in the Workplace in the Audiovisual and Performing Arts Industry in Latin America” - FIA-LA; UNI Americas MEI (International Federation of Actors et UNI Americas MEI / Panartes, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

#MeToo: Theatre Women Share Their Stories - Heyliger, Yvette (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

A Single Drop of Water: Vulnerability, Invisibility, and Accountability in South Korean Theatre’s Moment of Crisis - Younghee, Park; Neideck, Jeremy (Performance Paradigm, 2020)
In early 2018, encouraged by the #MeToo movement sweeping the Western media landscape, Korean actor Park Younghee took to Facebook to write of her experiences of sexual harassment at the hands of a prominent theatre director and academic in the 1990s. While Younghee didn’t publicly name her abuser, it was not long before the social media machine identified Oh Tae Suk as the man she alluded to, and his world-renowned Geukdan Mokwha as the site of her abuse. Days later, prolific theatre director Kim Soo-hee made allegations of violence and sexual abuse against Lee Yoon-taek, the artistic director of the juggernaut theatre company Yeonhuidan Georipae, setting off a firestorm in the South Korean Media that has yet to die down. In South Korea, public performances of grief, allyship, and holding the government to account are hallmarks of democratic transformation. In this article, Park Younghee tells parts of her story to longtime collaborator Jeremy Neideck, and they attempt to weave a coherent narrative out of their yearlong discussion about the social, cultural, and political histories of Korea. This article seeks to illuminate, but not necessarily explain, the environments in which men like Lee Youn-taek and Oh Tae Suk were able to perpetrate abuse.
Keywords: Bibliographie; Nettoyer; Raphaël

A Nonbinary Actor Prepares (for Battle) - Woodzick, K. Bylines (Theatre Topics, 2020)
Keywords: Bibliographie; Nettoyer; Raphaël

Considering Queerness - Actor Training's Issues and Alternatives - LeBlanc, Jacob G. (Université du Commonwealth de Virginie, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

Contemporary Feminist Protest in Ireland: #MeToo in Irish Theatre - Fitzpatrick, Lisa (Irish University Review, 2020)
This essay draws upon the work of Judith Butler, Sara Ahmed, and Germaine Greer to consider the #MeToo movement and its reflection in the work of the author's students and the scandal at Dublin's G...
Keywords: #MeToo; Bibliographie; Contemporary Feminism; Intergenerational; Intersectional; Nettoyer; Raphaël; Teaching

#MeToo In Polish Theatre Education - Kwaśniewska-Mikuła, Monika (Philosophy, Sociology, Psychology and History, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Le point de vue des improvisatrices au sujet des inégalités et des stéréotypes de genre véhiculés en improvisation théâtrale et ce que ceux-ci révèlent sur la société : Une recherche en travail social féministe - Robert Durant, Catherine (Université du Québec à Montréal, 2020)
Keywords: Bibliographie; Coffre à outils; Nettoyer; Sophie-Anne

Jouer Sur le Banc Les Filles Dans le Monde de L'improvisation. - Walsh-Viau, Emmanuelle.; Joubert, Lucie (Somme Toute, 2022)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Portrait de la pratique de l'improvisation théâtrale en milieu scolaire et plan d'action pour son optimisation - Garneau, Jocelyn (L'escabeau, 2021)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Rapport de recherche sur l'état du milieu du spectacle d'improvisaiton théâtrale au Québec - Garneau, Jocelyn (Le théâtre de la Ligue Nationale d'Improvisation et la Rencontre Théâtre-Ados de Lavac avec l'appui financier du Ministère de la Culture et des Communications du Québec, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

SPEAK OUT: together for a safer circus - Fédération européenne des écoles de cirque (FEDEC); JUMP (2023)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Violences à caractère sexuel: Les actes « graves » de Samuel Archibald - Perron, Louis-Samuel (La Presse, 2022)
L’écrivain réputé Samuel Archibald a profité de son statut de professeur de littérature pour avoir des relations sexuelles avec deux étudiantes sous son autorité, conclut une enquête indépendante commandée par l’Université du Québec à Montréal (UQAM). Une de ces femmes l’accuse même de l’avoir étranglée lors d’une relation sexuelle non consentie. Des actes « graves » et « hostiles » qui ont mené à son départ en catimini de l’UQAM l’an dernier.
Keywords: Bibliographie; Irina; Nettoyer

Recommandations - Rudesse (Facebook, 2020)
Keywords: Bibliographie; Dans le rapport; Sophie-Anne

Il était une fois... de trop - Institut national de l'image et du son. (2024)
Une formation pour prévenir le harcèlement en culture.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

“She’s just another pretty face:” sexual harassment of female photographers - Somerstein, Rachel (Feminist Media Studies, 2021)
This article examines sexual and gendered harassment among professional female editorial photographers, whose experiences have largely been under-researched. It draws on semi-structured interviews conducted between 2017–2019 with 17 female professional editorial photographers, aged 23–82, who work in a variety of beats. Sixteen of 17 interviewees encountered sexual harassment, with gendered harassment the most common. Harassers included professors, other photographers, colleagues, salespeople, subjects, and the general public, whom photographers encountered at school, work, while networking, and when using and buying gear. Largely, participants addressed the sexual and gendered harassment on an individual level, rather than reporting it to editors or other authorities. These findings add qualitative nuance to quantitative research that suggests physical risks and economic precarity may drive women from the profession.
Keywords: Bibliographie; Embodiment; Myriam; Nettoyer; Sexual harassment; female journalists; gender and work; photographers; photojournalism

Patriarchal pits: the gendered experiences of female concert photographers - Lough, Kyser (Journal of Gender Studies, 2020)
While the presence of women in photojournalism is increasing, the way they are treated by their male counterparts remains unbalanced. Drawing from feminist theory and embodiment, this study examines how the gendered experience plays out for women in a particular niche of photojournalism; concert photography. The restricted access of the music scene and the embodied nature of photojournalism combine to present unique barriers for women. In-depth interviews with male and female concert photographers show women still face a form of patriarchal oppression in the field. This is seen through gendered language, such as ‘one of the guys’ versus a ‘mom in the pit’, embodied actions such as direct sexual harassment or indirect benevolent sexism, and in how women are questioned when they identify themselves as a photographer.
Keywords: Bibliographie; Myriam; Nettoyer; Photojournalism; concert photography; embodiment; feminist theory

Rapport de recherche sur l’éthique en regard des violences à caractère sexuelle dans le milieu de l’humour québécois francophone - Bernier, Dominique; Paré, Christelle; Carbonneau, Karine; Vernus, Judith; Morency, Sophie-Anne (UQÀM et partenaires, 2022)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Sexual Harassment in Display Work: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Gender & Society, 2021)
Keywords: Bibliographie; Cultural industries; Display work; Fashion; Informal industries; Modeling industry; Myriam; Nettoyer; Power dynamics; sexual harassment

How Independent Contractors Respond to Sexual Harassment: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Employee Responsibilities and Rights Journal, 2022)
Sexual harassment continues to be a problem that most commonly affects women in the United States workforce today. While there are legal and organizational remedies available, most of these mechanisms for redress only exist for workers in traditional employeremployee contexts. Independent contractors, self-employed workers who represent a growing number of labor force participants in this economy, can therefore only use informal means of addressing sexual harassment. This study used grounded theory methods to analyze 88 separate narratives of sexual harassment from 70 fashion models, an overwhelmingly female set of independent contractors currently operating in the American economy. The aim of the analysis was to understand the mix and meaning behind the use of informal strategies—more specifically confrontation versus non-confrontation—in response to this sexual harassment. Notably, models most often confronted the perpetrators of harassment. Critically, however, those models who chose non-confrontation did not minimize the abuse that they faced. Instead, they either saw themselves as powerless or engaged in self-blame when faced with harassment on the job.
Keywords: Bibliographie; Confrontation; Fashion industry; Independent contractors; Models; Myriam; Nettoyer; Sexual harassment

Challenging gendered power: How sexual harassment perpetrators respond to victim confrontation - Crowley, Jocelyn Elise (Gender, Work & Organization, 2023)
Sexual harassment is a problem that continues to plague mostly women in the American workforce today. One tool that victims can use in these situations is confrontation, either through verbal or physical means. Yet, understudied to this point is how perpetrators respond to confrontation, which is highly salient as to whether this is an effective tool for victims. This study uses grounded theory methods to analyze 31 accounts of sexual harassment from within the fashion industry that recorded perpetrators' responses to victim confrontation to clearly unwanted, abusive behavior. I argue that specific features of the fashion industry, or a “display work culture,” embolden perpetrators to effectively thwart any type of confrontation. Indeed, this study finds that these predominantly male perpetrators of sexual harassment moved to reassert their dominant position over their female victims in the moment of confrontation, immediately after being confronted, and even later, well beyond confrontation, as they aimed to reestablish normal business practices as usual. This research thus dispels a significant sexual harassment myth that victims working within this culture are able to stop perpetrators simply by speaking up and/or fighting back and points to the need for the development of sexual harassment theory to incorporate work culture-related risk factors and remedies.
Keywords: Bibliographie; Myriam; Nettoyer; confrontation; display work culture; fashion industry; perpetrators; sexual harassment

An Examination on Sexual Harassment Activities in the South African Professional Performing Arts Industry - Yende, Sakhiseni Joseph (Journal of African Films & Diaspora Studies, 2021)
Keywords: Bibliographie; Nettoyer; Patriarchal power; Performing arts industry; Professional theatres; Raphaël; Sexual harassment; Women in theatre

La quatrième vague du féminisme : quel impact sur le champ littéraire ? - Mairesse, Lise (Université catholique de Louvain, 2022)
Keywords: Bibliographie; Irina; Nettoyer

Title IX, Esports, and #EToo - Stoever, Jane K (The George Washington Law Review, 2021)
As colleges and universities increasingly award video gaming scholarships, field competitive esports teams, construct esports arenas in the centers of campuses, and promote student interaction through gaming, schools should anticipate the sexual cyberviolence, harassment, and technology-enabled abuse that commonly occur through gaming.
Keywords: Bibliographie; Irina; Nettoyer

Gendered Barriers In The Gaming Industry - Singh, Tanya (Journal of Sports Law, Policy and Governance, 2020)
As of 2019, there are an estimated 2.5 billion garners globally. Roughly half of all garners are female. Despite the figures, there is a serious underrepresentation of female gainers in the professional gaming and game development community. It is thus important to examine the underlying causes hindering equally capable female gainers and game developers from pursuing a serious career in gaming, at par with their male counterparts.In this article, the authorexamines the impact of the culturalassociationof games with the male demography, stereotypes andstructuralbarrierslimiting women from realizing theirfullpotential, female representation in video games and workplace, pervasive misogyny and sexual harassment of women across all levels in the industry, and lastly, the steps that can be taken to better the status quo in favour of women.
Keywords: Bibliographie; Irina; Nettoyer

Exploring Vicarious Liability to Remedy the #E-Too Movement - Hewson, Eloise (York Law Review, 2022)
The esports, or competitive video gaming, industry is an exciting area of economic and cultural growth. Gaming can facilitate interpersonal connection, shared problem-solving, and creativity. Players may purchase a game, watch a streamer play it online, join an online gaming community, attend a tournament, compete professionally, or find employment in game development or a related field. The gaming industry generates enormous economic value and employs tens of thousands of people in the UK alone. However, the esports sector does not extend its benefits equally. Women are regularly verbally harassed in video games, countless women have been groped at esports events, women have been raped by professional players, underage fans have been groomed. Abuse is endemic to online gaming communities.
Keywords: Bibliographie; Irina; Nettoyer

Politique visant à prévenir et à combattre les violences à caractère sexuel (Annexe E) - École nationale de l'humour (2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

#ThisIsArtSchool Is Exposing Allegations Of Racism & Sexual Abuse In Montreal Universities - Elliot, Teddy (MTL Blog, 2020)
As stories of racism and discrimination towards Black, Indigenous, and people of colour continue to dominate public discourse, more and more shocking allegations come to light about the lived experiences of systemic racism.
Keywords: Bibliographie; Nettoyer

Designing Women: Learning from Feminist Legacies and the Women-In-Games Movement - Schoemann, Sarah (Georgia Institute of Technology, 2021)
In 2019 the video games industry was rocked by a slew of high-profile sexual harassment and assault allegations that some called the #MeToo movement of the games world, but to many these revelations came as no surprise. From the 2004 EA Spouse controversy to the 2014 #Gamergate harassment campaign the games industry has long been known for harboring an at times toxic atmosphere of exploitation and discrimination. This project looks at a handful of Women-In-Games organizations that set out to change the experience of women in the industry by helping newcomers to gain high tech skills and to supporting early career professionals through mentorship and community building. Along the way, it combines the study of these Women-In-Games organizations with a years-long collaboration bringing video games to the US' oldest feminist bookstore, Charis Books & More in Atlanta, GA. Through examining the work and values of two types of organizations devoted to women's equality, one a historic feminist movement-building space and the others, contemporary interventions into the professional games and tech industry, this study asks the questions "What can the Women-In-Games movement learn from the rich history of feminist organizing at spaces like Charis?" "Can games play a part in feminist movement building?" and "What does the future of feminist organizing look like in the games industry?”
Keywords: Bibliographie; Irina; Nettoyer

Let Her Play: A report on gender-based violence in video games - Mettler, Kirsten (Embodied: The Stanford Undergraduate Journal of Feminist, Gender, and Sexuality Studies, 2022)
Globally, video games are a $152 billion industry, and approximately 3.1 billion people, or 40% of the population, are players (Ingersoll & Anti-Defamation League, 2019, Price, 2020). Gaming is a huge industry, and it’s only getting bigger. Unfortunately, women and other historically marginalized groups often face staggering levels of harassment and violence in these communities. This report aims to explore the issue of gender-based violence in video games by analyzing contributing factors and proposing gaming company interventions.
Keywords: Bibliographie; Irina; Nettoyer; esports

We protect animals well": A structural approach to abusive conduct within circus schools - Matthis, Rosa (Linköping University, 2021)
This master thesis investigates abusive conduct in circus schools. Focus is put on the management level in order to achieve and provide knowledge of measures and attitudes related to prevention. Th ...
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Les expériences des victimes de violence sexuelle dans les programmes de justice réparatrice - Wemmers, Jo-Anne; Parent, Isabelle; Casoni, Dianne; Quirion, Marika Lachance (Centre international de criminologie comparée, 2020)
Keywords: Bibliographie; Expérience; Justice; Nettoyer; Système judiciaire; Victimes; Violence

Are Female Clowns Politically Incorrect? A Case Study on Female Clowns’ Political Engagement at the 7th “Esse Monte de Mulher Palhaça” festival in Rio de Janeiro - Cézard, Zed (Cadernos de Arte e Antropologia, 2020)
By linking the notion of politics with clown practices played out during the biennial festival «Esse Monte de Mulher Palhaça» in Rio de Janeiro (2018), dedicated specifically to female clowns, the relations between politics and feminism are raised, as well as the question of the place of clowns and women within the social system in which they act. In addition to reassessing the concept of politics through this new field of application, looking at what artistic practices convey or denounce as inequalities, allows us to identify politicized and political social elements. The private sphere, the power relations, the importance of gender, and the body and sexuality as treated in the festival’s performances raise political issues. We are lead to think of the phenomenon of Brazilian female clowns as a political space of claims, in particular feminist ones, and a resistance to dominant sexist normativity.
Keywords: Bibliographie; Brazil; Nettoyer; Sophie-Anne; female clowns; feminism; activism; politics

#TimesUp on Individual Litigation Reform: Combatting Sexual Harassment through Employee-Driven Action and Private Regulation - Dugan, Natalie (Columbia Journal of Law and Social Problems, 2020)
Keywords: Bibliographie; Irina; Nettoyer

Women actors, insecure work, and everyday sexism in the Canadian screen industry - Liinamaa, Saara; Rogers, Malia (Feminist Media Studies, 2022)
Acting, especially in the screen arts industry, is a job where women are subjected to pronounced and widely accepted socio-cultural aesthetic ideals within an industry that has become renowned for its tolerance for and justifications of sexism and sexualized violence. However, there is a limited amount of scholarship that examines actors and acting from a work and employment perspective. Drawing on the literature on work insecurity and gender inequities in cultural work, this article examines the screen industry from the perspective of women actors in a semi-peripheral location in Canada. This is a cohort that has managed to remain in the industry, despite high levels of attrition. Drawing on in-depth semi-structured interviews, our participants identify a range of strategies they employ (toughness, silence, humour, refusal, creative resistance) to respond to workplace sexism and gender-based constraints as they try to balance their creative agency with career sustainability. Participants emphasized that finding multiple outlets for realizing creative agency is crucial to counteracting everyday sexism and remaining in the industry.
Keywords: Bibliographie; Irina; Nettoyer; Screen industry; everyday sexism; gender and cultural work; women actors and acting

The impact of #MeToo in the South African film and television industry, within a historical framework - Majiba, Ntsika (Université de l'Afrique du Sud, 2022)
The study is a history project and is concerned with tracking the impact of #MeToo in the South African Film and Television industry in South Africa. Its main premise were the findings made public by a South African organization, Sisters Working in Film and Television (SWIFT) in 2017, that found that sexual harassment in the television and film industry was not just a norm but a crisis. The core focus of the study was on the development and impact of the #MeToo movement, which entailed investigating the manner in which women reacted to the hashtag (#MeToo), the reaction of their male counterparts, as well as the reaction and actions taken by the various bodies, institutions and organisations in the Film and Television industry, which included; broadcasters and production houses alike. This study begins by giving a concise background of the movement by firstly, historicising various female-led movements and comparing and contrasting them with the rise of digital movements or digital activism. The historicisation involves a brief comparison of past and present women-led activism, as well as a brief review of other hashtags like #AmINext and #Enough, on which #MeToo has had an influence. It goes on to investigate the development of #MeToo movement and to discuss the responses of the industry and individuals to the movement. The study embarked on a data collection quest by interviewing eleven female television and film practitioners in South Africa. Their ages ranged from 20 to 55. The findings of the research revealed that female practitioners were still being harassed post #MeToo, although subtly. The lack of unity amongst women in the sector was cited as one of the reasons behind the ongoing harassment. Gender parity and equity was also still lacking in the South African television and film industry. This study emerged in the midst of activism and scholarship seeking to unravel the norms of South African sexual harassment and rape culture against women. Thus, the study focused on the changes and transformations brought about by the hashtag within the industry. With South Africa’s historical background and the current circumstances around Gender Based Violence (GBV), this study was concerned with tracking whether or not digital activism had in some way been able to aid change and transformation. In particular, this study looked at the impact of the MeToo phenomenon on the women in the industry, the extent to which it empowered them, what they began to say and how they began to act. The study also explored South Africa’s ‘rape culture’ as South Africa has been proclaimed the ‘worlds rape capital’. It reflected on the colonial rule as the perpetuation of patriarchy and male entitlement over female bodies. Patriarchy in the industry was also confirmed by the findings and through data analysis, as one of the key factors in the emergence of #MeToo in South Africa, and in the utilisation of the hashtag by women in the sector to speak up against sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

Gender Equality in British Film-making: Research, Targets, Change - Cobb, Shelley; Williams, Linda Ruth (Women in the International Film Industry: Policy, Practice and Power, 2020)
In October 2017, the British Film Institute declared that it would commit to specific targets for gender equality and diversity in key production roles on films with support from the Film Fund. This decision by the BFI to set targets, arguably, did not come just from their own diversity and inclusion goals. Activist film-makers had previously called for targets for the Film Fund, especially for women directors. This chapter will give an accounting of the current state of gender (in)equality in the UK industry by: outlining new research that has clarified the stagnant inequality in the UK film industry; articulating the key role of a network of activist groups (that include researchers, professional and campaigning bodies, exhibitors and film-makers) to bring attention to the problem; putting pressure on the film industry and public bodies; and summarising institutional responses to that pressure since 2016, with a critical analysis of the potential and limits of the BFI’s relatively recently implemented diversity and equality targets.
Keywords: Bibliographie; Irina; Nettoyer

Sexual violence and nightlife: A systematic literature review - Quigg, Zara; Bigland, Charlotte; Hughes, Karen; Duch, Mariangels; Juan, Montse (Aggression and Violent Behavior, 2020)
Preventing and responding to sexual violence in nightlife settings is increasingly of global concern. The goal of this article was to identify and summarise academic studies on nightlife-related sexual violence. Specifically, to explore the nature, extent and consequences of, or associations with nightlife-related sexual violence, and interventions to prevent and respond. Of the 61 studies identified, 29 explored or reported on the nature of nightlife-related sexual violence, 22 provided information on extent, 38 on associations, and 19 on prevention and response. The majority of studies had been implemented in the past ten years (2009–2018) and in high-income countries. The review illustrates that nightlife-related sexual violence is pervasive, with lifetime prevalence reaching over 50% amongst numerous study samples. Studies suggest that a combination of factors at an individual, relationship, and community/environmental level is associated with nightlife-related sexual violence. No studies directly explored consequences, and few studies evaluated prevention and response approaches. Globally, further research is required to understand nightlife-related sexual violence, and inform the development of prevention programmes across all but particularly low and middle-income countries. Critically, interventions aimed at preventing and responding to nightlife-related sexual violence require thorough evaluation, with findings disseminated in both lay and academic literature.
Keywords: Bars; Bibliographie; Nettoyer; Nightlife; Prevention; Rape; Sexual; Violence

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (Australian & New Zealand Journal of Criminology, 2020)
Despite the well-documented under-reporting of sexual violence, to date, no research has considered reporting practices within the specific context of music festivals. Drawing on 16 in-depth interviews with victim-survivors, this article examines survivors’ experiences of (non)reporting sexual violence in festival settings. We argue that while some barriers to reporting are shared across contexts, others play out in context-specific ways. Our research argues that the liberal, often transgressive culture of music festivals, combined with site-specific policing practices and spatial context, creates unique impediments to reporting with particular implications in responding to, and aiming to prevent, sexual violence at music festivals.
Keywords: Bibliographie; Camille; Nettoyer

Laughter from the Sidelines: Precarious Work in the Canadian Comedy Industry - Trusolino, Madison (Creative Industries in Canada, 2022)
Creative Industries in Canada is a foundational text that encourages students to think critically about creative industries within a Canadian context and interrogate the current state and future possibilities of the industry. While much of current creative industries literature concerns the United Kingdom, the United States, and Asia, this text captures the breadth of how Canadian industries are organized and experienced, and how they operate.This ambitious collection aims to guide students through the current landscape of Canadian creative industries through three thematic sections. “Production” collects chapters focused on how national discourses and identities are produced through creative industries and the tensions that exist between policy and media. “Participation” explores how we engage with these industries in different roles: as consumer, creator, policy-maker, and more. “Pedagogies” explores how education impacts inclusion and visibility in creative industries.Truly intersectional, Creative Industries in Canada provides students with practical industry knowledge and frameworks to explore the current state of the field and its future. With a broad application to many undergraduate programs, this text is a must-read resource for those pursuing media studies, arts management, creative and cultural industries studies, communications, and arts and humanities.
Keywords: Bibliographie; Business & Economics / Industries / Media & Communications; Nettoyer; Social Science / Media Studies; Sophie-Anne

Louis C.K.’s time’s up time out: rereading persona post-scandal - Piper, Melanie (Celebrity Studies, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Can You Come Back from Being Cancelled? A Case Study of Podcasting, Cancel Culture, and Comedians during #MeToo - Holman, Kylie J. (University of Nebraska, 2020)
Cancel culture is a new phenomenon of public shaming, facilitated by social media. This type of public shaming is accepted due to the alleged transgression of those who are cancelled. Social understanding of cancel culture does not generally allow for redemption. Using the theoretical framework of Feminist Media Studies (Van Zoonen, 1994) and Media Framing Theory (Gitlin, 1980), this study reveals the media’s role and power in the cancelling process. This study utilized a mixed-methods approach of case study and text analysis of episodes from the pop culture and politics podcast, Keep It. The case study focused on podcast episodes pertaining to two comedians cancelled for allegations of sexual misconduct in the #MeToo era [Oct. 2017 – Present]: Aziz Ansari and Louis C.K. The study also provided comparative cases of other comedians and comedic actors who were cancelled. Findings add to our understanding of cancel culture and appropriate methods of redemption for those who are cancelled.
Keywords: #MeToo; Bibliographie; Cancel culture; Comedians; Nettoyer; Podcasting; Redemption; Sophie-Anne

Comedy in the Era of #MeToo: Masking and Unmasking Sexual Misconduct in Stand-Up Comedy - Oppliger, Patrice; Mears, Kathryn (The Dark Side of Stand-Up Comedy, 2020)
With the announcement of allegations of sexual harassment and sexual assault against beloved comedians, we ask, “Can one separate the art from the artist?” Comedians are supposed to bring audiences joy and laughter; however, this role is challenged when there is incongruity between the comic persona and the real-life misdeeds of comedians. We explore the rise of the #MeToo movement and the role of comedy in exposing as well as masking allegations against Bill Cosby, Louis C.K., Al Franken, and Aziz Ansari. Guided by disposition theory and disengagement models, findings reveal factors of race, gender, and personal relationships appear to influence comedians’ assessment of fellow comedians accused of sexual misconduct. Audience members also appear to experience moral disengagement.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Caste, gender, and “global Indian-ness”: spaces of safety in stand-up comedy in global Mumbai - James, Aju (Feminist Media Studies, 2022)
This paper argues that stand-up comedy produces the places it uses in the city of Mumbai as “safe” for new middle-class women by excluding Dalit and working-class people who are deemed “dangerous.” Such exclusion is achieved by mobilising places and infrastructure that are built to make Mumbai a “world-class” city, a process that requires the dispossession and exploitation of the masses from which the new middle-class benefits. In the context of the sexual harassment charges that hit the stand-up comedy scene in 2018 and the responses to those charges, I posit that stand-up comedy is a site where “appropriate” gender hierarchies are formulated in the pursuit of “global Indian-ness.”
Keywords: Bibliographie; Global Indian-ness; Mumbai; Nettoyer; Sophie-Anne; sexual harassment; stand-up comedy; world-class city

Sexual Violence and Gender Equality in Grassroots Music Venues: How to Facilitate Change - Hill, Rosemary Lucy; Megson, Molly (IASPM Journal, 2020)
Sexual violence in the music industry is known to impact negatively on women’s participation. We examine how grassroots venues and promoters can implement changes to tackle sexual violence and work towards gender equality. We draw on UK-based, impact-focused research which sought to raise awareness of sexual violence, and to facilitate anti-violence changes within organisations. We find that working across a city’s music scene and engaging with oversight organisations such as local authorities can aid in persuading venues and promoters to seek training. However, for individuals leading on changes, personal experiences of sexual violence as a victim/survivor or bystander are important factors in their decision. We conclude that men in the music industry need to become more aware of the need for change, and willing to act on that awareness; and that more women need to own, manage, and run venues and events.
Keywords: Bibliographie; Gender; Nettoyer; live music; music industry; music venues; prevention; sexual violence